2015
DOI: 10.1051/0004-6361/201526688
|View full text |Cite
|
Sign up to set email alerts
|

Proper motions and membership probabilities of stars in the region of globular cluster NGC 6366

Abstract: Context. NGC 6366 is a metal-rich globular cluster that is relatively unstudied. It is a kinematically interesting cluster, reported as belonging to the slowly rotating halo system, which is unusual given its metallicity and spatial location in the Galaxy. Aims. The purpose of this research is to determine the relative proper motion and membership probability of the stars in the region of globular cluster NGC 6366. To target cluster members reliably during spectroscopic surveys without including field stars, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…11 the global abundance pattern for NGC 6366, with star 05 highlighted. As previously discussed in Section 4.1, Sariya & Yadav (2015) gave zero membership probability to star 05 based on its proper motion, while our radial velocity measurements suggest a value compatible with NGC 6366 kinematics. Chemically, this star follows the general abundance pattern of the GC.…”
Section: Global Abundance Patternsupporting
confidence: 78%
See 1 more Smart Citation
“…11 the global abundance pattern for NGC 6366, with star 05 highlighted. As previously discussed in Section 4.1, Sariya & Yadav (2015) gave zero membership probability to star 05 based on its proper motion, while our radial velocity measurements suggest a value compatible with NGC 6366 kinematics. Chemically, this star follows the general abundance pattern of the GC.…”
Section: Global Abundance Patternsupporting
confidence: 78%
“…Using the cross-correlation method, Johnson et al (2016) found a mean heliocentric RV of −122.3 km s −1 (σ = 1.5 km s −1 ) for NGC 6366. The proper motion analysis of Sariya & Yadav (2015) gave zero membership probability for star 05 and membership probability > 0.95 for stars 03, 07, 08 and 11. Stars 01, 06 and 11 were not present in their study.…”
Section: Kinematicsmentioning
confidence: 96%
“…The kinematic study of a cluster is important in determining membership of the cluster stars as determination of the membership is essential in the accurate estimation of cluster parameters (e.g., Chen et al 2011;Sariya & Yadav 2015). The major difficulty in determination of the cluster parameters using isochrone fitting is contamination by the field stars.…”
Section: Proper Motion Membershipmentioning
confidence: 99%
“…Our research group derived proper motions and membership probabilities for the stars in the area of globular clusters NGC 6809, NGC 6366 and NGC 3201 (Sariya et al 2012(Sariya et al , 2015(Sariya et al , 2017. Number of the studied stars is ∼12600, 2530 and 8322 for NGC 6809, NGC 6366 and NGC 3201 consecutively.…”
Section: Resultsmentioning
confidence: 99%
“…Devesh P. Sariya, Ing-Guey Jiang & R. K. S. Yadav Reference stars to calculate proper motions were selected using the position of stars in the color-magnitude diagrams (CMD) and then, the program was iterated to include good proper motion. The detailed procedures to obtain the proper motion has been discussed by A06; Bellini et al (2009); Yadav et al (2008Yadav et al ( , 2013; Sariya et al (2012Sariya et al ( , 2015Sariya et al ( , 2017. A centroid around the cluster proper motion center in the vector point diagrams gives the cluster members.…”
mentioning
confidence: 99%